2017
DOI: 10.3390/su9091599
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of a Dual-Chamber Oscillating Water Column Wave Energy Converter

Abstract: Abstract:The performance of a dual-chamber Oscillating Water Column (OWC) Wave Energy Converter (WEC) is considered in the present study. The device has two sub-chambers with a shared orifice. A two-dimensional (2D) fully nonlinear numerical wave flume based on the potential-flow theory and the time-domain higher-order boundary element method (HOBEM) is applied for the simulation. The incident waves are generated by using the immerged sources and the air-fluid coupling influence is considered with a simplified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Dual-chamber devices were installed on a floating breakwater for wave energy extraction by He et al (2012He et al ( , 2013. A dual-chamber OWC-WEC, which has two subchambers with a shared orifice, was proposed by Ning et al (2017), and the effects of the chamber geometry on the variation of surface elevation and water column volume in the two subchambers were studied. accurately measure the wave power of floating OWC with wider chamber breadth in the experiments for the first time and discussed the power extraction performance of a floating breakwater with dual-chamber devices.…”
Section: Introductionmentioning
confidence: 99%
“…Dual-chamber devices were installed on a floating breakwater for wave energy extraction by He et al (2012He et al ( , 2013. A dual-chamber OWC-WEC, which has two subchambers with a shared orifice, was proposed by Ning et al (2017), and the effects of the chamber geometry on the variation of surface elevation and water column volume in the two subchambers were studied. accurately measure the wave power of floating OWC with wider chamber breadth in the experiments for the first time and discussed the power extraction performance of a floating breakwater with dual-chamber devices.…”
Section: Introductionmentioning
confidence: 99%
“…Their results show that the overall performance of the proposed device, compared with the single-chamber OWC device, can be significantly improved over a wider incident wave-frequency range. A fixed OWC WEC, which is composed of two sub-chambers with a shared orifice, was explored by Ning et al [16], using the higher-order boundary element method to mainly examine the effects of the chamber geometry on the surface elevations and pressure drops inside these two sub-chambers. They concluded that the fluctuation of water columns was strongly dependent on the wave properties, and a larger wavelength could lead to a more violently oscillating water surface.…”
Section: Introductionmentioning
confidence: 99%
“…Rezanejad et al (2013Rezanejad et al ( , 2015 adopted BEM method to analyse 2 the efficiency of a two-dimensional nearshore multiple OWC devices placed over flat bottom and 3 stepped bottom, respectively. Ning et al (2015Ning et al ( , 2017) applied a fully nonlinear numerical wave 4 flume based on higher-order BEM in simulating of both one-chamber and dual-chamber OWC 5 devices. Numerical results indicated that the surface elevations in the two sub-chambers are 6 strongly dependent on the wave conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Falnes and McIver (1985) applied analytical method to study the 24 power absorption by an OWC, which is composed of two vertical barriers with unequal length, 25 oscillating in the surge mode. It was shown that all of the incident wave power can be captured by 26 the system with optimum values of the complex oscillation amplitudes. Sarmento analytically investigated by Boccotti (2007) and Malara and Arena (2013).…”
Section: Introductionmentioning
confidence: 99%